NO x and Hydrocarbon Trapping and Conversion in a Sequential Three-Zone Monolith: Spatiotemporal Features - Gupta, Abhay; Ambast, Mugdha; Harold, Michael P. (ACS Engineering Au, 2022)
The spatiotemporal features of the multifunctional monolithic lean hydrocarbon NO x trap (LHCNT), for eliminating NO x (x = 1 and 2) and ethylene (C2H4), are examined using spatially resolved mass spectrometry (SpaciMS), spanning the sequentially positioned passive NO x adsorber (PNA; Pd/SSZ-13), hydrocarbon trap (HCT; Pd/BEA), and oxidation catalyst (OC; Pt/Al2O3–CeO2). The overall LHCNT performance is captured in temporal trapping efficiency profiles, which show the integral NO and C2H4 uptake followed by delayed NO release along with NO and ethylene oxidation. Spatially resolved transient concentration profiles spanning uptake, release, and conversion of NO, H2, and C2H4, alone or as mixtures in feeds containing H2O, provide detailed insight into the transient coupling not attainable with effluent concentration monitoring alone. The PNA serves as the primary zone for NO uptake, followed by the OC and HCT. NO oxidation to NO2 occurs during NO uptake in the PNA due to Pd(II) reduction, while more extensive oxidation occurs in the OC at higher temperature. C2H4 uptake and oxidation occur in each of the functions with oxidation occurring the earliest (lowest temperature) in the OC. NO uptake in the PNA and HCT is negligibly affected by H2 but protracted oxidation of H2 during the temperature ramp delays NO release, suggesting persistence of NO bound on Pd(I). Both the PNA and HCT exhibit excellent C2H4 uptake, which diminishes in the presence of NO. Spatially resolved concentration data reveal several interesting features, such as high-temperature, sequential NO oxidation (by O2 to NO2) and C2H4 oxidation (by NO2 to NO + CO2) in the PNA. Simulated warmup experiments reveal that the LHCNT NO trapping is enhanced with C2H4 addition but that a reduction in space velocity may be needed to improve performance. A previously developed PNA model predicts satisfactorily the main features of spatially resolved NO and NO + C2H4 data.